Monte Mozinho. Uma cerâmica de pasta branca - Carvalho, Teresa Pires de (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
A particular roman ceramic of white fabric was found at Monte Mozinho, which is a romanized Northern Portuguese iron age hillfort, occupied from Ist to Vth centuries AD. This particular fabric was characterized and isolated from a large sample of white fabric pottery, and both macroscopic and chemical analyses were done in order to establish the origin of this pottery. However some questions remain unanswered, one was able to ascertain the chronology of this pottery production – end of Ist century BC to mid Ist century AD – as well as its area of production: somewhere in the south of Iberian Peninsula.